Nrf2 Ameliorates DDC-Induced Sclerosing Cholangitis and Biliary Fibrosis and Improves the Regenerative Capacity of the Liver. (2nd March 2019) - Fragoulis, Athanassios; Schenkel, Julia; Herzog, Miriam; Schellenberg, Tim; Jahr, Holger; Pufe, Thomas; Trautwein, Christian; Kensler, Thomas W; Streetz, Konrad L; Wruck, Christoph Jan
Abstract: The Nrf2 pathway protects against oxidative stress and induces regeneration of various tissues. Here, we investigated whether Nrf2 protects from sclerosing cholangitis and biliary fibrosis and simultaneously induces liver regeneration. Diet containing 3, 5-diethoxycarbonyl-1, 4-dihydrocollidine (DDC) was fed to Nrf2-KO mice (Nrf2 −/− ), mice with liver-specific hyperactivated Nrf2 (HKeap1 −/− ) and wild-type (WT) littermates to induce cholangitis, liver fibrosis, and oval cell expansion. HKeap1 −/− -mice were protected from almost all DDC-induced injury compared with WT and Nrf2 −/− . Liver injury in Nrf2 −/− and WT mice was mostly similar, albeit Nrf2 −/− suffered more from DDC diet as seen for several parameters. Nrf2 activity was especially important for the expression of the hepatic efflux transporters Abcg2 and Abcc2-4, which are involved in hepatic toxin elimination. Surprisingly, cell proliferation was more enhanced in Nrf2 −/− - and HKeap1 −/− -mice compared with WT. Interestingly, Nrf2 −/− -mice failed to sufficiently activate oval cell expansion after DDC treatment and showed almost no resident oval cell population under control conditions. The resident oval cell population of untreated HKeap1 −/− -mice was increased and DDC treatment resulted in a stronger oval cell expansion compared with WT. We provide evidence that Nrf2 activation protects from DDC-induced sclerosing cholangitis and biliary fibrosis. Moreover, our data establish a possible role of Nrf2 in oval cell expansion.